Edukasi Gizi Ibu Hamil dalam Pencegahan Stunting di Wilayah Kerja Puskesmas Baolan Kabupaten Tolitoli - Hasni, Hasni; Saman, Saman; Evie, Sova (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Pregnant women experiencing malnutrition at Puskesmas Baolan represent a pressing issue requiring special attention. Therefore, an intervention in the form of education is essential. The goal of this Community Service (Pengabdian Masyarakat or Pengabmas) activity is to enhance the knowledge of pregnant women regarding nutrition during pregnancy, enabling them to comprehend and fulfill their nutritional requirements during the gestation period, ultimately aiding in the prevention of stunting. This activity is executed through a lecture method employing tools such as Power Point and projection devices like infocus/LCD, along with question-and-answer sessions and discussions. The target audience for this endeavor comprises 58 pregnant women in Kelurahan Nalu, within the jurisdiction of Puskesmas Baolan, Tolitoli Regency. The results of the post-test conducted showed an increase in knowledge from 52% to 84%. While attitudes increased from 86% to 100%. In conclusion, it can be deduced that this educational initiative enhances the knowledge and alters the attitudes of pregnant women regarding nutrition during pregnancy. It is hoped that midwives and responsible parties involved in the nutrition program at Puskesmas Baolan can provide education on maternal nutrition at least monthly to improve pregnant. Women's understanding of meeting their nutritional requirements during the pregnancy period.